Microsporogenesis in angiosperms producing pantoporate pollen. Issue 4 (2nd October 2019) - Prieu, Charlotte; Toghranegar, Zohreh; Gouyon, Pierre-Henri; Albert, Béatrice
ABSTRACT: Pollen grains are produced during meiosis (microsporogenesis), in the anthers of flower buds. Apertures are usually formed at the last points of contact between the microspores. However this mechanism is not universal, and cannot explain aperture determination in species with more apertures than there are points of contact. Here, we study pollen development in pantoporate species (multi-aperturate) to understand what mechanism could account for aperture determination in this case. Twelve species producing pantoporate pollen were collected. They represent both monocots and eudicots. Microsporogenesis in these species was observed using epifluorescence microscopy with aniline blue coloration, which enabled us to observe callose. The features of microsporogenesis (cytokinesis, intersporal wall formation and tetrad form) in species with pantoporate grains do not differ strongly from the standard developmental pathway in monocots and eudicots, although tetrad form is more variable in pantoporate species. We identified additional callose deposits in microspores after the formation of the callose walls within tetrad, correlated with subsequent aperture position of the pollen grain. The number, relative size and density of these deposits are similar to those of the apertures in mature pollen grains. Additional callose deposits are likely to be involved in aperture determination, although the precise cellular mechanism of their involvement is not yet understood. Such callose deposits are present in phylogenetically distant species, suggesting that they have appeared several times independently in angiosperms.